Komunikasi Partisipatif dalam Upaya Konservasi Burung di Desa Jatimulyo, Kabupaten Kulonprogo - Yohanes Maharso Joharsoyo (School of Communication Science and Media Business, 2023)
Jatimulyo village was one of the groups that had performed the conservation to address the scarcity of birds. The movement is claimed to involve local participation. The study aims to describe participative communication in the jatimulyo bird conservation efforts in the Kabupaten Kulonprogo. It is a qualitative study using case-study methods. The data collection technique in this study was by doing focus group discussion (FGD) and observation. FGD has seven individuals, a representative of the forestry group of women and a representative of the Desa Jatimulyo. The study shows that participative communication needs to be improved. Because the communities are placed as passive objects, there is a dominant one, an undemocratic decision, no return, and limited access is given to communities to get through. Keywords: bird conservation, environmental movement, farmer’s group, community participation, participative communication